AI in material science revolutionizing construction in the age of Industry 4.0 - Saad, Syed; Ammad, Syed 1995-; Rasheed, Kumeel 1991- (CRC Press, 2024)
"AI in Material Science: Revolutionizing Construction in the Age of Industry 4.0 is a comprehensive guide for professionals and researchers in the fields of artificial intelligence, material science, and construction. The book explores the latest research and developments in the field of AI-assisted material science, and its use to revolutionize the construction industry in the age of Industry 4.0. The book provides real-world examples and case studies of AI-assisted material science in the construction sector, giving readers practical and actionable insights. It covers a wide range of applications of AI in material science, from design and modeling to fabrication and construction, making it a valuable resource for professionals in the field. The book also focuses on how artificial intelligence in material science can help drive the construction industry towards Industry 4.0, making it an important resource for professionals looking to stay ahead of the curve in this rapidly advancing field"--
Includes bibliographical references and index. - Description based on print version record
Keywords: Materials science -- Data processing; Artificial intelligence; Building -- Data processing; Industry 4.0; Science des matériaux; Informatique; Intelligence artificielle; Construction; Informatique; Industrie 4.0; artificial intelligence